Caught in the middle : neutrals, neutrality and the First World War - Hertog, Johan den, 1977-; Kruizinga, Samuël (Studies of the Netherlands Institute for War Documentation, 2011)
During the First World War, belligerents infringed on the rights and duties of neutrals, as these had been codified in international agreements. Both the Allies and the Central Powers pressured the neutrals to modify their policies in favour of one side or the other. During the four-and-a-half years the war lasted, this pressure mounted until the neutrals were left with very little room to manoeuvre. More than fifty years ago, Nils Ørvik stated that this disregard for international law, combined with the relative weakness of the European neutrals, spelled the end of traditional political neutra.